2019
DOI: 10.1128/aem.00956-19
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Release of Rare Earth Ions by Spores of Bacillus Species and the Location of These Ions in Spores

Abstract: Two rare earth ions, Tb3+ and Dy3+, were incorporated into spores of Bacillus species in ≤5 min at neutral pH to 100 to 200 nmol per mg of dry spores, which is equivalent to 2 to 3% of the spore dry weight. The uptake of these ions had, at most, minimal effects on spore wet heat resistance or germination, and the ions were all released upon germination, probably by complex formation with the huge depot of dipicolinic acid (DPA) released when spores germinate. Adsorbed Tb3+/Dy3+ were also released by exogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The PS533 strain was inserted with the Kar gene and is therefore resistant to kanamycin. The PS4150 strain was inserted with the tetR and spnR genes, replacing the cotE and gerE genes; therefore, it is resistant to spectinomycin and has a highly defective spore surface that lacks most spore coat proteins [5,21].…”
Section: Bacterial Strains and The Preparation Of Cells And Sporesmentioning
confidence: 99%
See 2 more Smart Citations
“…The PS533 strain was inserted with the Kar gene and is therefore resistant to kanamycin. The PS4150 strain was inserted with the tetR and spnR genes, replacing the cotE and gerE genes; therefore, it is resistant to spectinomycin and has a highly defective spore surface that lacks most spore coat proteins [5,21].…”
Section: Bacterial Strains and The Preparation Of Cells And Sporesmentioning
confidence: 99%
“…Rare earth ions are difficult to separate from each other due to their similar chemical properties, ionic radii, and trivalent positive charge [4]. The complexity of this task, coupled with the demand for environmentally friendly technologies, is driving the development of biohydrometallurgy [5]. Compared with chemical precipitation, dissolution extraction, ion exchange, and membrane separation, biosorption is a more environmentally friendly, Minerals 2022, 12, 866 2 of 14 efficient, and economical technique for the treatment and recovery of REEs [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core water content of spores was determined on both intact spores and spores that were chemically decoated as described (Dong et al . 2019), by layering ˜100 μl with ˜10 7 spores on a step gradient of Histodenz from 51 to 70% with fifteen 200 μl steps of 2%. The samples were then centrifuged at 5000 g min −1 for 45 min at 20°C in a swinging bucket rotor in a TLS‐55 rotor (Beckman Coulter Life Sciences, Brea, CA), the location at which the spores banded determined by inspection and the core wet density and the water content were calculated as described previously (Lindsay et al .…”
Section: Methodsmentioning
confidence: 99%
“…While most previous studies utilized growing bacteria to absorb REEs, a few reports have examined REE absorption by bacterial spores (86). Notably, Dong et al recently reported that B. subtilis spores could be a candidate for the adsorption of the REEs Tb 3ϩ and Dy 3ϩ (87). They found that Tb 3ϩ and Dy 3ϩ are incorporated into spores' outer layers (Fig.…”
mentioning
confidence: 99%